2013
DOI: 10.1159/000353676
|View full text |Cite
|
Sign up to set email alerts
|

Focal Cortical Subarachnoid Hemorrhage Revealed by Recurrent Paresthesias: A Clinico-Radiological Syndrome Strongly Associated with Cerebral Amyloid Angiopathy

Abstract: Background: Focal subarachnoid hemorrhage (SAH) is often revealed by transient and recurrent focal neurological episodes. This cause is important to identify because it carries a high risk of intracerebral hemorrhage (ICH). We report the clinical, imaging and prognostic data of 17 patients with focal SAH revealed by short episodes of paresthesias mimicking transient ischemic attacks. Methods: The medical records and imaging data of patients with focal acute SAH at the cerebral convexity and at least one episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…A previous study has correlated TFNE with SS in CAA patients who had suffered lobar ICH [7]. Several case series have suggested that CAA could be common cause of cSAH in the elderly [11,12]. Additionally, two recent studies in CAA with lobar ICH demonstrated that those with SS/cSAH had a higher risk of recurrent ICH compared with those without [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has correlated TFNE with SS in CAA patients who had suffered lobar ICH [7]. Several case series have suggested that CAA could be common cause of cSAH in the elderly [11,12]. Additionally, two recent studies in CAA with lobar ICH demonstrated that those with SS/cSAH had a higher risk of recurrent ICH compared with those without [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this 2 out of 17 CT scans were negative for fSAH compared to MRI in the series of Apoil et al, but also in this publication no detailed information on timing and physical acquisition parameters of the CT examination was given [15]. …”
Section: Discussionmentioning
confidence: 59%
“…The small number of cases acquired and the retrospective design of our study limits general recommendations from our data and does not allow a statistically valuable sensitivity/specificity analysis, as in previously published works [2,3,5,9,15]. Due to the short period between clinical onset and CT examination, we might have not missed one of the fSAH in CT.…”
Section: Discussionmentioning
confidence: 79%
“…This phenomenon is most closely associated with the neuroimaging finding of superifical siderosis on susceptibility-weighted sequences on MRI (see Fig. 1) [18]. This is most likely a focal epileptiform process, although others have suggested it is related to cortical spreading depression [19].…”
Section: Clinical Presentations Of Caamentioning
confidence: 90%